Green antibacterial molecules: sophorolipids with varying fatty acid chain - Hirlekar, Swarali; Abhyankar, Isha; Kane, Kartiki; Trimukhe, Kalpana; Prabhune, Asmita; Nisal, Anuya (Trends in Biomaterials and Artificial Organs, 2021)
Antibiotic resistance is a rising problem of over the last decade making it difficult to treat infections caused by various pathogenic bacteria. To tackle this problem, newer antimicrobial strategies are being explored. Sophorolipids (SLs) are a class of biomolecules produced by a non-pathogenic yeast Starmarella bombicola (S. bombicold) with surfactant as well as potent broad spectrum antibacterial activity. In this work, we have successfully synthesized sophorolipids using different fatty acids with increasing chain length of hydrophobic tail; Lauric acid (C12)-LASL, Myristic acid (C14)-MASL, Palmitic acid (C16)-PASL and Stearic acid (C18)-SASL. We have used various techniques like FTIR, HRMS to characterize the synthesized SL. Further, we have measured properties like the critical micellar concentration for these biosurfactants and the SL's showed CMC less than or equal to 100 mg/L indicating excellent surface-active property. We have studied the antibacterial activity against gram-negative and gram-positive bacteria. Interestingly, the antibacterial activity was found to be more potent as the chain length of the fatty acid in the SL decreased. This trend was found to be reverse for toxicity towards mammalian cells. The shorter chain fatty acid SL's were found to be less cytotoxic. These results indicate that the sophorolipid candidates with shorter chain lengths would be beneficial for various biomedical applications such as tissue engineering, regenerative medicine and wound healing. Keywords: sophorolipid, biosurfactant, short chain fatty acid, antibacterial
Keywords: Antibacterial agents; Cells (Biology); Infection; Microbial drug resistance; Saturated fatty acids; Surface active agents

Silk fibroin and recombinant elastin blend nano-coatings for implantable medical devices - Joseph, Emmanuel; Kane, Kartiki; Parekh, Nimisha; Nisal, Anuya; Janorkar, V. Amol (Materials Today Communications, 2022)
Silicone breast implants are conventionally used to reconstruct the shape and size of the breast in breast cancer patients. However, rate of failure of implants due to formation of capsular contracture is significantly high. Recent studies have shown that coating the surface of the implant with a biocompatible polymer can mitigate this risk. Here, we have modified the surface of implant using a biocompatible natural biopolymer silk fibroin (SF). Further, we have developed formulations of SF with a recombinantly produced elastin-like-peptide (ELP) and compared their performance with a known anti-fouling hydrophilic polymer - polyethylene oxide (PEO). Microscopic and spectroscopic characterization confirm the formation of uniform coatings. These coatings have been also characterized for their ability to resists crack formation. Further, the coatings have been evaluated for their biological performance. Our studies show that addition of 25 wt% of ELP to SF significantly enhances the crack resistance for the coatings. In addition, SF/ELP coatings reduce the adsorption of blood plasma proteins by more than 80 %. Preliminary analysis shows that the SF/ELP blend coatings are non-cytotoxic and support adhesion, growth and proliferation of fibroblast cells. The study therefore demonstrates that SF/ELP coatings have the potential to mitigate the risk of breast implant failure.
Keywords: Blood plasma; Crack resistance; Protein adsorption; Recombinant elastin; Silk fibroin

Superior processability of Antheraea mylitta silk with cryo-milling: performance in bone tissue regeneration - Parekh, Nimisha; Bijosh, C. K.; Kane, Kartiki; Panicker, Alaka; Nisal, Anuya; Wangikar, Pralhad; Agawane, Sachin (International Journal of Biological Macromolecules, 2022)
Non-mulberry silk polymers have a promising future in biomedical applications. However, the dissolution of nonmulberry silk fiber is a still challenge and this poor processability has limited the use of this material. Here, we report a unique protocol to process the Antheraea mylitta (AM) silk fiber. We have shown that the cryo-milling of silk fiber reduces the beta sheet content by more than 10% and results in an SF powder that completely dissolves in routine solvents like trifluoroacetic acid (TFA) within few hours to form highly concentrated solutions (\~20 wt %). Further, these solutions can be processed using conventional processing techniques such as electrospinning to form 3D scaffolds. Bombyx mori (BM) silk was used as a control sample in the study. In-vitro studies were also performed to monitor cell adhesion and proliferation and hMSCs differentiation into osteogenic lineage. Finally, the osteogenic potential of the scaffolds was also evaluated by a 4-week implantation study in rat calvarial model. The in-vitro and in-vivo results show that the processing techniques do not affect the biocompatibility of the material and the AM scaffolds support bone regeneration. Our results, thus, show that cryo-milling facilitates enhanced processability of non-mulberry silk and therefore expands its potential in biomedical applications.
Keywords: Bone tissue engineering; Calvarial defect; hMSCs; Non-mulberry silk fiber; Processing technique